2021
DOI: 10.3390/biology10090829
|View full text |Cite
|
Sign up to set email alerts
|

Type I Interferons in COVID-19 Pathogenesis

Abstract: Among the many activities attributed to the type I interferon (IFN) multigene family, their roles as mediators of the antiviral immune response have emerged as important components of the host response to Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection. Viruses likewise have evolved multiple immune evasion strategies to circumvent the host immune response and promote virus propagation and dissemination. Therefore, a thorough characterization of host–virus interactions is essential to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 99 publications
1
23
0
Order By: Relevance
“…A highly impaired IFN‐I response is known to underlie severe COVID‐19 [1–3]. In a subset of COVID‐19 patients, the defect is explained by the presence of auto‐Abs against IFN‐I [8, 10–12].…”
Section: Discussionmentioning
confidence: 99%
“…A highly impaired IFN‐I response is known to underlie severe COVID‐19 [1–3]. In a subset of COVID‐19 patients, the defect is explained by the presence of auto‐Abs against IFN‐I [8, 10–12].…”
Section: Discussionmentioning
confidence: 99%
“…However, IFNs show differential associations with clinical markers of poor prognosis and COVID-19 severity (38). Regarding IFN-I's role in COVID-19, it was demonstrated that numerous SARS-CoV-2 proteins have the ability to inhibit IFN-I production and/or IFN-I responses (39), producing resistance to this antiviral mechanism (40). Although viruses display strategies to evade the IFN antiviral activity, there are host-factors that affect the severity of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been demonstrated that insufficient antiviral IFN-I responses are the hallmark of COVID-19 infection ( Lin and Shen, 2020 ). Several SARS-CoV-2 proteins, including nucleocapsid (N), membranous (M), and nonstructural (NS) proteins, inhibit the production of IFN-Is ( Palermo et al, 2021 ). On the other hand, the result of multiplexed single-cell epitope and transcriptome sequencing revealed the dysfunction of ISG responses in patients with severe COVID-19 ( van der Wijst et al, 2021 ).…”
Section: Anti–ifn–i Autoantibody In Covid-19: Immunopathogenesis and ...mentioning
confidence: 99%